Toradora!. Vol. 10 - Takemiya, Yuyuko, 1978- (Seven Seas, 2020)
With both Ryuuji and Taiga<U+2019>s mothers seemingly determined to tear them apart, the newly minted teenage lovebirds hatch a dicey elopement plan that<U+2019>s going to depend on Minori, Ami, and Kitamura<U+2019>s help to succeed. Will their friends come through for them at the crucial moment? Or is happily-ever-after just a childish fantasy? Find out in this heart-stopping conclusion to the epic romcom!